2021
DOI: 10.1111/jors.12537
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants, voter sentiment, and local public goods: The case of museums

Abstract: We present a model where museum commitment to immigrant integration is conditioned by the possible negative reactions of native visitors and patrons. We then exploit the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the global context of immigration, studying the phenomenon at a regional level is arousing much interest among scholars [12][13][14][15]19]. Dirksmeier (2021) states that although regionalism per se does not influence the feeling of hostility towards immigrants, local economic disparities may accentuate a trend of negative attitudes towards immigrants.…”
Section: Theorical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the global context of immigration, studying the phenomenon at a regional level is arousing much interest among scholars [12][13][14][15]19]. Dirksmeier (2021) states that although regionalism per se does not influence the feeling of hostility towards immigrants, local economic disparities may accentuate a trend of negative attitudes towards immigrants.…”
Section: Theorical Backgroundmentioning
confidence: 99%
“…Dalle Nogare et al [19] presented a cross-country analysis across Italian territories and found that the increase in the population support to some anti-immigration parties may be negatively correlated with the presence of public policies that are addressed to immigrants' integration, such as free or discounted access to museums.…”
Section: Theorical Backgroundmentioning
confidence: 99%